KEBERADAAN KERAJINAN LOGAM DI TUMANG CEPOGO BOYOLALI - Darmojo, Kuntadi Wasi (Institut Seni Indoensia Surakarta, 2018)
ABSTRACT Metal Crafts in Tumang, Cepogo, Boyolali, is one of the nation's cultural assets that has been passed down through generations from generation to generation, which is still occupied by the majority of Tumang people. The tradition of making products in Tumang metal handicrafts has undergone significant changes, where from the beginning of its establishment until before the 1960s, the results of products oriented to household items, then in the early 1970s until now have experienced object-oriented product changes ornamental.Factors that cause cultural change through new products include: internal and external factors, impulses and direction of the process of change (innovation), as well as various phenomena of socio-cultural change. Internal factors are driven by the creativity of metal craft makers, while external factors are triggered by scholars, artists, or other innovation figures.Changes in Tumang metal handicraft products have implications for the community, marked by a professional division of labor and the establishment of new institutions. The existence of metal crafts in Tumang, as an art product in society is still accepted in accordance with the development and changes in civilization of its supporting society.Â Keywords: crafts, metals, Tumang, changes and products